2020
DOI: 10.1088/1748-3190/ab9a14
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired robotic fish utilizes the snap-through buckling of its spine to generate accelerations of more than 20g

Abstract: Inspired by the fastest observed live fishes, we have designed, built and tested a robotic fish that emulates the fast-start maneuver of these fishes and generates acceleration and velocity magnitudes comparable to those of the live fishes within the same time scale. We have designed the robotic fish such that it uses the snap-through bucking of its spine to generate the fast-start response. We have used a dynamic snap-through buckling model and a series of experiments on a beam under snap-through buckling to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Fishes first bend their body to C-shape and then recoil their body quickly to accelerate. Gazzola identified the C-start pattern which minimize the escape distance and Currier designed a robotic fish that can generates fast-start accelerations of more than 20g by utilizing a dynamic snap-through buckling mechanism [85,113]. As for turning locomotion, a fundamental life function, fish can use it to change swimming direction frequently and flexibly for finding food or mates.…”
Section: Intermediate Viewmentioning
confidence: 99%
“…Fishes first bend their body to C-shape and then recoil their body quickly to accelerate. Gazzola identified the C-start pattern which minimize the escape distance and Currier designed a robotic fish that can generates fast-start accelerations of more than 20g by utilizing a dynamic snap-through buckling mechanism [85,113]. As for turning locomotion, a fundamental life function, fish can use it to change swimming direction frequently and flexibly for finding food or mates.…”
Section: Intermediate Viewmentioning
confidence: 99%
“…These animals engage their musculature and translate a moving wave along the body to the tail tip to produce thrust for swimming. BCF locomotion can be represented as a sinusoidal waveform which is restricted by a polynomial envelope, as shown in Equation (1). The respective constraints of this motion are dependent on the animal to be replicated [15].…”
Section: Bioinspired Prescribed Motion Of Body Caudal Fin Carangiform Auvmentioning
confidence: 99%
“…Aquatic unmanned vehicles (AUVs) are being developed and advancing into bioinspired body undulating-oscillatory locomotion, replicating fishes [1,2]. Typical aquatic systems are rigid-bodied, controlled with propellers and often tethered [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the swimming ability and environmental adaptability were limited because the system relied on the front-facing oscillator to generate backward fish waves instead of a distributed drive system. Currier et al [11] reported a dependent bio-inspired fish with airbags wrapped around a central elastic layer. The fish could be bent by applying pressure to one side, and the mechanism of the rapid C-shaped start of the fish was elucidated.…”
Section: Introductionmentioning
confidence: 99%